The Impact of Age on Seizure Severity Characteristics in Children With Drug Resistant Epilepsy - Tria Diana Lestari; Ika Citra Dewi Tanjung; Syamsidah Lubis; Juliandi Harahap; Johannes Harlan Saing; Wisman Dalimunthe (GLOBAL HEALTH SCIENCE GROUP, 2025)
Drug-resistant epilepsy (DRE) is found in up to one-third of individuals with epilepsy who have received appropriate therapy and this condition causes significant child morbidity and mortality. Epilepsy that appears at an early age is at higher risk of developing DRE. Objective to assess the effect of age on the characteristics of seizure severity in children with DRE. This study used a cross-sectional design involving 36 DRE patients aged 2-18 years at the Child Neurology Polyclinic, Adam Malik Hospital Medan, from September to October 2024. Seizure severity characteristics were assessed using the Global Assessment of the Severity of Epilepsy (GASE) questionnaire instrument. The categorical data are presented in the form of proportions and the effect of age on seizure severity characteristics was analyzed using the chi-square test. There were 36 children with DRE in this study, predominantly aged ≥ 10 years. Bivariate analysis showed a significant effect of age in children with drug resistant epilepsy only on the disruption of activity experienced by children with a p value = 0.036 (p <0.05). Most patients aged ≥ 10 years did not experience activity disorders or experienced mild activity disorders (73.9%), while in patients aged <10 years, most patients experienced severe activity disorders (61.5%). The age of children with drug resistant epilepsy have a significant effect on daily activity disorders.